PERBEDAAN TEKANAN DARAH SEBELUM DAN SETELAH OLAHRAGA JALAN KAKI PADA LANSIA DENGAN RIWAYAT HIPERTENSI - Hosen Hosen; Said Mardjanto; Firdha Novitasari (Jurnal Kesehatan dr. Soebandi, 2016)
The difference in blood pressure before and after exercise walking in elderly people with a history of hypertension in the Sumberbaru Health Center District of Jember recidence. Elderly is the process of becoming older with age reaching 45 years of age or older. The number of elderly in Indonesia amounted to 19.3 million (8.37%) of the total population of Indonesia), the number of elderly in Jawa Timur 11.16%. in Sumberbaru health centers in February 2014 there were as many as 45 elderly people suffering from hypertension. The aim of this study was to analyze differences in blood pressure before and after exercise walking in elderly people with a history of hypertension. The research is a Quasi-Experiment with design one group pre-test post-test design. The population in this study amounted to 45 people. Sample size is 12 people with porpusive sampling technique. Research results obtained by the average blood pressure before walking downhill after walking 1.7611 by 0.083 into 1.528, Based on the paired t test obtained results that the significance value of 0.000> 0.05, meaning that there is a difference walking on blood pressure. The conclusion of this study there was no difference in blood pressure before and after exercise walking in elderly people with a history of hypertension in the Sumberbaru Health Center District of Jember recidence